Outcomes of fetuses with severe diaphragmatic hernia after fetal endoluminal tracheal occlusion treatment: A series of case reports - ChunYan Zhong; XiaoHang Zhang; SuZhen Ran (Taiwanese Journal of Obstetrics & Gynecology)
Objective: To explore outcomes of fetuses with severe congenital diaphragmatic hernia (CDH) after fetal endoluminal tracheal occlusion (FETO) treatment. Case report: Fetuses diagnosed with severe CDH and taken FETO for intrauterine treatment from January 2020 to December 2023 were recruited. There was no significant difference in general conditions, as well as O/E LHR and measurements related to CDH (p > 0.05). All babies were born prematurely. One got poor Apgar score and died soon after birth and 3 died after treatment in NICU for some time. Only one associated with congenital cystic adenomatoid malformation (CCAM) was survived and got good outcome after long time follow-up. It seemed CCAM associated occupying a part volume of left thorax which may help to protect abdominal organs from herniating. Conclusion: FETO treatment may not improve the survival rate of severe CDH significantly, but associated with CCAM may helpful to protect abdominal organs from herniating.